Development of a multi-residue method for the determination of human and veterinary pharmaceuticals and some of their metabolites in aqueous environmental matrices by SPE-UHPLC–MS/MS - Paíga, P. (2016)
The aim of the present work was to develop and validate a multi-residue method for the analysis of 33 human and veterinary pharmaceuticals (non-steroidal anti-inﬂammatory drugs (NSAIDs)/analgesics, antibiotics and psychiatric drugs), including some of their metabolites, in several aqueous environ-mental matrices: drinking water, surface water and wastewaters. The method is based on solid phase extraction (SPE) followed by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS) and it was validated for different aqueous matrices, namely bottled water, tap water, seawater, river water and wastewaters, showing recoveries between 50% and 112% for the majority of the target analytes. The developed analytical methodology allowed method detection limits in the low nanograms per liter level. Method intra- and inter-day precision was under 8% and 11%, respectively, expressed as relative standard deviation. The developed method was applied to the analysis of drinking water (bottled and tap water), surface waters (seawater and river water) and wastewaters (wastewater treatment plant (WWTP) inﬂuent and efﬂuent). Due to the selectivity and sensitivity of the optimized method, it was possible to detect pharmaceuticals in all the aqueous environmental matrices considered, including in bottled water at concentrations up to 31 ng L−1 (salicylic acid). In general, non-steroidal anti-inﬂammatory drugs/analgesics was the therapeutic group most frequently detected, with the highest concentrations found in wastewaters (acetaminophen and the metabolite carboxyibuprofen at levels up to 615 and 120 g L−1, respectively).